Nursing of a patient with epigastric pain treated by acupoint finger-pressing combined with Traditional Chinese Medicine ointment rubbing therapy (手指点穴联合中药膏摩治疗胃脘部胀痛1例的护理体会) - LU Xiaofang (逯小芳); DIAO Xinyue (刁欣悦); LI Ke (李可); LIU Haiyang (刘海洋) (中西医结合护理)
This article summarized the nursing of a patient with epigastric pain treated with acupoint finger-pressing therapy combined with Traditional Chinese Medicine ointment rubbing therapy. Key issues of nursing included nursing assessment, lifestyle guidance, diet nursing, acupoint finger-pressing and Traditional Chinese Medicine ointment rubbing therapy. Based on the acupoints selection by syndrome differentiation, the acupoint finger-pressing and Traditional Chinese Medicine ointment rubbing therapy had successfully relieved the epigastric pain symptoms of the patient. (本文总结手指点穴联合中药膏摩治疗1例胃脘部胀痛患者的护理体会, 包括护理评估、生活指导、饮食护理、手指点穴以及中药膏摩操作方法等。根据辩证分析选取穴位, 配合常规护理, 运用手指点穴联合中药膏摩的护理方法能够有效缓解患者胃脘部胀痛症状。)